2020
DOI: 10.1111/iwj.13485
|View full text |Cite
|
Sign up to set email alerts
|

Role of hospital anxiety and depression on the healing of chronic leg ulcer: A prospective study

Abstract: A chronic leg ulcer is a debilitating illness, owing to the local condition of the wound and a decrease in physical activity and productivity, resulting in anxiety and depression among patients. The study aimed to find any association of anxiety and depression in the healing of chronic wounds. A total of 125 patients with chronic leg ulcers were enrolled in the study. HADS questionnaire assessment followed the local wound examination in all patients. A follow‐up assessment of the ulcer was done after appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These ulcers can be debilitating, having a major impact on a person's life, often with disease distress symptoms including pain, decreased physical functioning, immobility, sleep disturbance, lack of energy, limitations in leisure activities, worries and frustrations, lack of self-esteem and a substantial negative impact on health-related quality of life 13 . Many published studies report risk factors for delayed/ non-healing of VLUs [14][15][16][17][18][19] ; however, to date, there have been no systematic reviews that we could find and only limited reviews of risk factors [20][21][22][23] , particularly those that include non-physiological factors, due to a range of definitions, methodological inconsistencies in data collection, and measurement of risk factors 20 . Previously reported studies have consistently concluded risk factors as being a larger ulcer area, a longer ulcer duration, a previous history of ulceration, venous abnormalities and a lack of high compression 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These ulcers can be debilitating, having a major impact on a person's life, often with disease distress symptoms including pain, decreased physical functioning, immobility, sleep disturbance, lack of energy, limitations in leisure activities, worries and frustrations, lack of self-esteem and a substantial negative impact on health-related quality of life 13 . Many published studies report risk factors for delayed/ non-healing of VLUs [14][15][16][17][18][19] ; however, to date, there have been no systematic reviews that we could find and only limited reviews of risk factors [20][21][22][23] , particularly those that include non-physiological factors, due to a range of definitions, methodological inconsistencies in data collection, and measurement of risk factors 20 . Previously reported studies have consistently concluded risk factors as being a larger ulcer area, a longer ulcer duration, a previous history of ulceration, venous abnormalities and a lack of high compression 20 .…”
Section: Introductionmentioning
confidence: 99%